"What does it mean for our family?": learning from paediatric patient journeys. (24th May 2012) - Macaulay, CP; Fertleman, CR
Abstract : UCL's intercalated BSc (iBSc) in Paediatrics in Child Health began in 2010. The iBSc aims to further education in Paediatrics at an Undergraduate level, to promotoe academic paediatrics, and to excite a cohort of medical undergraduates about the possibilities of a career in Paediatrics by giving them learning opportunities and experiences not normally accessed in the medical undergraduate curriculum. The course has two main strands: how patients and families travel through and experience healthcare - "the patient journey" - and research within paediatrics. Learning from cases is central to the study of medicine, yet often the patient experience is lost. We feel that this experience of illness is central to understanding the full implications of long-term conditions, and makes individuals more insightful practitioners. Students follow "patient journeys" in several ways. They are given "patient journeys" as written stories. These are real stories collected from families given in instalments with questions for reflection and discussion. A Paediatrician and a Child Psychiatrist facilitate discussions. Students have to write a reflective essay on one of the issues that have arisen for one of the families as part of their assessment. Additionally students spend regular sessions talking to families, children and teenagers about their experiences of illness. Students also collect their own "patient journey" from families of children with long-term conditions. This usually involves interviewing them in their home setting. Common themes that emerge in these sessions include the importance of communication, difficulties in dealing with different professionals and uncertainty. Feedback from both students and participating families is overwhelmingly positive. One student commented "..the iBSc gave me a better appreciation of the way in which small actions of members of the medical professions could have huge impacts on the family - both positive and negative". Families valued the opportunity to "tell their story" and one commented "..if it makes them a better doctor then we have both benefited" Learning directly from patient experience is increasingly being recognised but is still not fully embedded in many undergraduate (or postgraduate) paediatric curricula. We hope to extend the scope of this work and make our teaching tools widely available for medical education purposes.